Порівняльна характеристика широти сполучуваності на семантичному рівні у публіцистичному, науковому та художньому стилів сучасної англійської мови х - Данилович, Оксана Дмитрівна; Тоненчук, Тетяна Василівна; Мудра, Олена Василівна (My University, 2023)
The article has been devoted to the investigation of width combinability on the semantic level in the publicistic, scientific and belle-lettres styles. The object of the study is semantic combinability of adjectives with nouns, the subject is the study of width combinability on the semantic level. The goal of our investigation is to compare width combinability of LSG of adjectives with LSG of nouns in three styles. A high index of width combinability for all three styles was defined for LSG of adjectives “Field of activity”, “Estimation of value, meaning, quality and function”, “Estimation of the object by form, volume, size” with a high usage frequency. The style factor influences neither the width combinability nor the usage frequency of these three LSG of adjectives. The same width of combinability was determined for the publicistic and belle-lettres styles for the LSG of adjectives “Nationality”, “Geographical position”, “Estimation of the object by space, distance, duration”. In the belle-lettres and scientific styles the same number of syntagmatic partners was found as “Intensity and measure”, “Administrative, regional, class distinctions”. For the belle-lettres style the highest indices of width combinability were distinguished for LSG of adjectives “Estimation of the object in comparison with signs of others”, “Age, time”, “Colour”, “Emotional state, feelings”, “Behaviour and actions to the object”, “Natural and physical state”, “Traits of character, habits”, “Appearance”, “Estimation of mental abilities of a man”, “Temperature”. The highest indices of width combinability for the publicistic style were found for “Intensity and measure”, “Administrative, regional, class distinctions”, “Religion, race”, “Speed”. For the scientific style the sign “Composition and material” is remarkable, it has the highest usage frequency though with the smallest number of syntagmatic partners which is caused by the style. The influence of the style factor on the width and the usage frequency of LSG was determined.
Keywords: width combinability, adjective, noun, lexical-semantic group